Fantastic 4 (2005) [videorecording (DVD)] - Story, Tim; Gruffudd, Ioan; Alba, Jessica, 1981-; Evans, Chris, 1981-; Chiklis, Michael, 1963- (20th Century Fox Home Entertainment, 2005)
After exposure to cosmic radiation, four astronauts become the most remarkable, if not most dysfunctional, superheroes of all time. Reed Richards is the leader of the group and gains the ability to stretch all parts of his body, he takes the name Mr. Fantastic. His girlfriend, Sue Storm, gains the ability to turn invisible and create force fields, calling herself the Invisible Woman. Her younger brother Johnny Storm gains the ability to control fire, including covering his own body with flame and is those named the Human Torch. Pilot Ben Grimm is turned into a super-strong rock creature and decides to call himself Thing. Together, they use their unique powers to explore the strange aspects of the world, and to foil the evil plans of Doctor Doom.